Application of Cu(I)-catalyzed azide–alkyne cycloaddition for the design and synthesis of sequence specific probes targeting double-stranded DNA - Vasilyeva, Svetlana V.; Filichev, Vyacheslav V.; Boutorine, Alexandre S. (Beilstein Journal of Organic Chemistry, 2016)
Efficient protocols based on Cu(I)-catalyzed azide–alkyne cycloaddition were developed for the synthesis of conjugates of pyrrole–imidazole polyamide minor groove binders (MGB) with fluorophores and with triplex-forming oligonucleotides (TFOs). Diverse bifunctional linkers were synthesized and used for the insertion of terminal azides or alkynes into TFOs and MGBs. The formation of stable triple helices by TFO-MGB conjugates was evaluated by gel-shift experiments. The presence of MGB in these conjugates did not affect the binding parameters (affinity and triplex stability) of the parent TFOs.
Keywords: binding affinity; click chemistry; Cu(I)-catalyzed azide–alkyne cycloaddition; pyrrole–imidazole polyamides; sequence specificity: DNA; triplex-forming oligonucleotides

(untitled) - Boutorine, A. S.; Novopashina, D. S.; Krasheninina, O. A.; Nozeret, K.; Venyaminova, A. G. (Molecules, 2013)

(untitled) - Nozeret, K.; Bonan, M.; Yarmoluk, S. M.; Novopashina, D. S.; Boutorine, A. S. (Bioorg. Med. Chem., 2015)

(untitled) - Nozeret, K.; Loll, F.; Escudé, C.; Boutorine, A. S. (ChemBioChem, 2015)

DNA Binders and Related Subjects - Escudé, C.; Sun, J.-S. (DNA Major Groove Binders: Triple Helix-Forming Oligonucleotides, Triple Helix-Specific DNA Ligands and Cleaving Agents, 2005)

(untitled) - Praseuth, D.; Guieysse, A. L.; Hélène, C. (Biochim. Biophys. Acta, Gene Struct. Expression, 1999)

(untitled) - Dervan, P. B.; Edelson, B. S. (Curr. Opin. Struct. Biol., 2003)

(untitled) - Blackledge, M. S.; Melander, C. (Bioorg. Med. Chem., 2013)

(untitled) - Melander, C.; Burnett, R.; Gottesfeld, J. M. (J. Biotechnol., 2004)

(untitled) - Vaijayanthi, T.; Bando, T.; Pandian, G. N.; Sugiyama, H. (ChemBioChem, 2012)

(untitled) - Szewczyk, J. W.; Baird, E. E.; Dervan, P. B. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Novopashina, D. S.; Sinyakov, A. N.; Ryabinin, V. A.; Venyaminova, A. G.; Halby, L.; Sun, J.-S.; Boutorine, A. S. (Chem. Biodiversity, 2005)

(untitled) - Trauger, J. W.; Baird, E. E.; Dervan, P. B. (J. Am. Chem. Soc., 1998)

(untitled) - Kers, I.; Dervan, P. B. (Bioorg. Med. Chem., 2002)

(untitled) - Halby, L.; Ryabinin, V. A.; Sinyakov, A. N.; Boutorine, A. S. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Kawamoto, Y.; Sasaki, A.; Hashiya, K.; Ide, S.; Bando, T.; Maeshima, K.; Sugiyama, H. (Chem. Sci., 2015)

(untitled) - Filichev, V. V.; Pedersen, E. B. (J. Am. Chem. Soc., 2005)

(untitled) - Doluca, O.; Boutorine, A. S.; Filichev, V. V. (ChemBioChem, 2011)

(untitled) - Doluca, O.; Hale, T. K.; Edwards, P. J. B.; González, C.; Filichev, V. V. (ChemPlusChem, 2014)

(untitled) - Mukaiyama, T.; Matsueda, R.; Suzuki, M. (Tetrahedron Lett., 1970)

(untitled) - Hashimoto, M.; Ueki, M.; Mukaiyama, T. (Chem. Lett., 1976)

(untitled) - Knorre, D. G.; Alekseyev, P. V.; Gerassimova, Y. V.; Silnikov, V. N.; Maksakova, G. A.; Godovikova, T. S. (Nucleosides Nucleotides, 1998)

(untitled) - Sinyakov, A. N.; Ryabinin, V. A.; Grimm, G. N.; Boutorine, A. S. (Mol. Biol., 2001)

(untitled) - Ryabinin, V. A.; Boutorine, A. S.; Hélène, C.; Denisov, A. Yu.; Pyshnyi, D. V.; Sinyakov, A. N. (Nucleosides, Nucleotides Nucleic Acids, 2004)

(untitled) - Ryabinin, V. A.; Boutorine, A. S.; Hélène, K.; Denisov, A. Yu.; Pyshnyi, D. V.; Sinyakov, A. N. (Russ. J. Bioorg. Chem., 2005)

(untitled) - Meldal, M.; Tornøe, C. W. (Chem. Rev., 2008)

(untitled) - Lutz, J.-F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Gutsmiedl, K.; Wirges, C. T.; Ehmke, V.; Carell, T. (Org. Lett., 2009)

(untitled) - Bernardin, A.; Cazet, A.; Guyon, L.; Delannoy, P.; Vinet, F.; Bonnaffé, D.; Texier, I. (Bioconjugate Chem., 2010)

(untitled) - Baskin, J. M.; Prescher, J. A.; Laughlin, S. T.; Agard, N. J.; Chang, P. V.; Miller, I. A.; Lo, A.; Codelli, J. A.; Bertozzi, C. R. (Proc. Natl. Acad. Sci. U. S. A., 2007)

(untitled) - Géci, I.; Filichev, V. V.; Pedersen, E. B. (Chem. – Eur. J., 2007)

(untitled) - Kupryushkin, M. S.; Konevetz, D. A.; Vasilyeva, S. V.; Kuznetsova, A. S.; Stetsenko, D. A.; Pyshnyi, D. V. (Nucleosides, Nucleotides Nucleic Acids, 2013)

(untitled) - Grimm, G. N.; Boutorine, A. S.; Helene, C. (Nucleosides, Nucleotides Nucleic Acids, 2000)

Proceedings of XX IS3NA IRT - Vasilyeva, S.; Filichev, V.; Silnikov, V.; Boutorine, A. (Application of "click chemistry" for design and sythesis of sequence-specific ligands and probes targeting double-stranded DNA, Montreal, Canada, 5.8.2012-9.8.2012)
http://www.is3na.org/assets/events/Category%202-Medicinal%20Chemistry%20of%20Oligonucleotides%20%2864-108%29.pdf

(untitled) - Halby, L.; Ryabinin, V. A.; Sinyakov, A. N.; Novopashina, D. S.; Venyaminova, A. G.; Grokhovsky, S. L.; Surovaya, A. N.; Gursky, G. V.; Boutorine, A. S. (J. Biomol. Struct. Dyn., 2007)

(untitled) - Giovannangeli, C.; Diviacco, S.; Labrousse, V.; Gryaznov, S.; Charneau, P.; Helene, C. (Proc. Natl. Acad. Sci. U. S. A., 1997)

Combinatorial Library, Methods and Protocols - Krutzik, P. O.; Chamberlin, A. R. (Synthesis of DNA-Binding Polyamides, 2002)

(untitled) - Krutzik, P. O.; Chamberlin, A. R. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Jacobsen, M. F.; Ravnsbæk, J. B.; Gothelf, K. V. (Org. Biomol. Chem., 2010)

(untitled) - Poulin-Kerstien, A. T.; Dervan, P. B. (J. Am. Chem. Soc., 2003)

(untitled) - Paramasivam, M.; Cogoi, S.; Filichev, V. V.; Bomholt, N.; Pedersen, E. B.; Xodo, L. E. (Nucleic Acids Res., 2008)

(untitled) - Globisch, D.; Bomholt, N.; Filichev, V. V.; Pedersen, E. B. (Helv. Chim. Acta, 2008)

Current Protocols in Nucleic Acid Chemistry - Boutorine, A. S.; Escudé, C. (UNIT 7.12 Biophysical Analysis of Triple-Helix Formation, 2007)

Twisted Intercalating Nucleic Acids (TINA) in Guanosine-rich Oligonucleotides - Doluca, O. (Massey University, 2013)